Diversity and distribution of yeasts in intertidal zones of China - Zhu, Hai-Yan; Han, Da-Yong; Guo, Liang-Chen; Li, Jun-Ning; Wei, Xu-Yang; Zhang, Ri-Peng; Wang, Qi-Ming; Shang, Yu-Jie; Luo, Lu-Jun; Wei, Yu-Hua; Liu, Xin-Zhan; Bai, Feng-Yan (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales, Saccharomycetales, Tremellales, Sporidiobolales, and Pichiales. The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.